Neurocysticercosis an uncommon intra-cerebral infection in Malaysia - Muthusamy, Kalai Arasu; Khairul, A.; Waran, V. (Malaysian Medical Association, 2005)
Neurocysticercosis, infection of the central nervous system (CNS) by larvae of the pork tapeworm Taenia solium, is the commonest neuroparasitic infection in humans. However in countries as in Malaysia it poses a diagnostic problem as the disease in not seen amongst the local population; however with the arrival of immigrant workers, a number of cases have recently been diagnosed. There were 3 cases of neurocysticercosis reported in our centre over the last 5 years.